Development Strategy for Food Security of Farmer Households in the Keduang Sub Watershed (DAS) in Wonogiri Regency - Setyarini, Agung; Arianti, Yoesti Silvana; Dewati, Rosita (Pascasarjana, Mataram University, 2024)
The purpose of this study is to determine the internal and external factors that affect the food security of farmer households, and formulate strategies for developing food security of farmer households. The novelty of this research is to obtain alternative strategies to improve food security of farmer households. The method of determining the research location was carried out purposively, and the determination of the sample research area was carried out purposively, so that 3 sub-districts were selected, namely Jatipurno (upstream), Jatisrono (middle) and Sidoharjo (downstream). Data collection methods were observation, interview, and FGD (Focus Group Discussion). The data analysis method used two stages, including: a) Input Matrix of Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE), and b) analysis using SWOT matrix. The results explained that there were 10 strengths, 11 weaknesses, 4 opportunities, and 5 threats. Based on the SWOT matrix, there are 12 alternative development strategies, namely: 1) increasing food availability of farmer households; 2) assistance by related agencies on food diversification, food safety and health; 3) reducing farming inputs; 4) increasing farmer household income; 5) training and counseling on nutrition; 6) making reservoirs; 7) incentives for millennial farmers; 8) using rice varieties that are low in emissions and resistant to pests and diseases; 9) government regulations on land use change; 10) adjustment of planting times and patterns; 11) selection of drought-resistant food crop commodities and 12) planting of plantation crops